2006
DOI: 10.1097/01.hjr.0000209813.05573.4d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of exercise training heart rate in patients on β-blockers after myocardial infarction

Abstract: The Karvonen formula underestimates the heart rate at the anaerobic threshold in beta-blocked patients, which may lead to undertraining of patients with coronary artery disease; we propose another formula more adapted to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 26 publications
(23 reference statements)
2
51
2
1
Order By: Relevance
“…The cardiopulmonary exercise test (CPET) determines the ventilatory threshold (VAT), 16 which is a useful guide to determining the target intensity level for the prescription of exercise in healthy individuals and those with cardiovascular disease. [17][18][19] Prescribing exercise at a percentage of the peak heart rate or VO peak 2 attained on a graded exercise stress test may result in a suboptimal training intensity in individuals who may prematurely terminate a stress test because of stroke-related factors unrelated to cardiovascular end points such as neuromuscular disability. 20 The VAT is a submaximal intensity measure that does not necessitate the achievement of a "true" VO max 2 (i.e., an individual's maximal capacity to transport and use oxygen), is achievable by most people post stroke, 20 and is an important measure for gauging and guiding the exercise intensity prescription.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiopulmonary exercise test (CPET) determines the ventilatory threshold (VAT), 16 which is a useful guide to determining the target intensity level for the prescription of exercise in healthy individuals and those with cardiovascular disease. [17][18][19] Prescribing exercise at a percentage of the peak heart rate or VO peak 2 attained on a graded exercise stress test may result in a suboptimal training intensity in individuals who may prematurely terminate a stress test because of stroke-related factors unrelated to cardiovascular end points such as neuromuscular disability. 20 The VAT is a submaximal intensity measure that does not necessitate the achievement of a "true" VO max 2 (i.e., an individual's maximal capacity to transport and use oxygen), is achievable by most people post stroke, 20 and is an important measure for gauging and guiding the exercise intensity prescription.…”
Section: Introductionmentioning
confidence: 99%
“…The CPET determines the ventilatory anaerobic threshold (VAT), which represents the movement from aerobic to anaerobic metabolism, 11 and is recommended as an appropriate target intensity level for the prescription of exercise. [12][13][14] Achievement of maximal oxygen uptake (VO 2max ; ie, an individual's maximal capacity to transport and use oxygen) is another important measure used to prescribe exercise intensity. Therefore, VO 2max , VAT, and the level at which a clinically relevant abnormality (CRA) occurs are all critical measures for prescribing an exercise intensity that is both safe and effective.…”
mentioning
confidence: 99%
“…In our study, we observed that the AMIG showed lower aerobic functional capacity both in the AT and at peak exercise compared to the CG, demonstrated by the power, HR, VO 2 30 and Tabet et al 33 . The lowest functional capacity values presented by AMIG, in both at the AT and at peak exercise, can be attributed to two distinct mechanisms: 1) the presence of pathology and 2) to the use of betablocker therapy.…”
Section: Discussionmentioning
confidence: 62%
“…In this sense, the AMIG underwent to sub-maximal CPET 22±4 days (on average) after the AMI, as well as in the studies of Tabet et al 33 and Duru et al 34 , which evaluated the patients at 18 and 36 days (on average) after the AMI, respectively. During the CPET, the AMIG have not presented any signs or symptoms that limited its performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation